KERAGAAN PROGRAM RASKIN DI KABUPATEN BANYUMAS - Hari Prasetyawadi (Universitas Muhammadiyah Purwokerto, 2014)
This study aims to determine the number of poor rice distributed by the government and the success rate Raskin program in Banyumas. The research was conducted with a sample survey method with 97 respondents (heads of households) drawn at random by using a multistages cluster rqndom sampling method. The data obtained were analyzed with descriptive analysis method. The results showed that the amount disbursed Raskin government from April 2012 increased from 2,117,565 kg to 2,233,605 kg or an increase of 116 040 kg, and the government has been quite successfully implement the program because it can reach three Raskin right, namely the right quality, on time, and the exact price of the target five right, while the right target and the right amount can not be done well